ANALISIS IMPLEMENTASI LAYANAN INOVASI SAMSAT KELILING DALAM UPAYA MENINGKATKAN PELAYANAN PEMBAYARAN PAJAK KENDARAAN BERMOTOR PADA UNIT PELAYANAN PENDAPATAN DAERAH PELAIHARI KABUPATEN TANAH LAUT - AFRIYANSAH; M. Riduan Abdillah; Marliza Noor Hayati (JRUP: JURNAL REFERENSI DAN ULASAN PERPAJAKAN, 2025)
The purpose of this study was to determine the application of Mobile Samsat innovation services. The research method used in this research is descriptive qualitative. The results of this study conclude that the Pelaihari Regional Revenue Service Unit Office as a public service provider through the innovation of the Mobile Samsat service has implemented services according to established procedures or flows so as to make it easier for people to pay taxes. The services provided to the community are in accordance with the service standards and service quality applied by the Mobile Samsat. This is in accordance with the people's desire to get a public service that is easy, fast, effective, and efficient so that later it can increase Motor Vehicle Tax revenue.